2022
DOI: 10.1002/htj.22532
|View full text |Cite
|
Sign up to set email alerts
|

Cattaneo–Christov heat flux model for nanofluid flow over a curved stretching sheet: An application of Stefan blowing

Abstract: The present work investigates the thermophoresis and Brownian motion effects in nanofluid flow over a curved stretching sheet (CSS). Also, the Cattaneo–Christov heat flux and Stefan blowing (SB) conditions are considered for studying heat and mass transport characteristics. The present work's novelty is associated with considerations of convective boundary and SB conditions in nanomaterial flow over a CSS. The coupled partial differential equations are changed to ordinary differential equations by employing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These important factors, too, optimize solar radiation. All these features are displayed in Figures (3)(4)(5)(6)(7)(8)(9) and are also presented in numerical tables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These important factors, too, optimize solar radiation. All these features are displayed in Figures (3)(4)(5)(6)(7)(8)(9) and are also presented in numerical tables.…”
Section: Discussionmentioning
confidence: 99%
“…Adding further for The charactistics of the hybrid nanofluids are displayed according to Table (1) and same as [9,28,29]).…”
Section: Thermo-physical Characteristicsmentioning
confidence: 99%
“…Rana and Gupta [17] analyzed the impacts of Marangoni convection and Stefan blowing in nanoliquid flow across an infinite disk. Kumar et al [18] demonstrated the mass transport features in double-diffusive nanofluid flow above a stretchable curved surface.…”
Section: Introductionmentioning
confidence: 99%
“…Radius also serves as a road speed restriction function in traffic circles. The effects of blowing on a second‐grade fluid stream across a curved surface with convective heating were discussed by Punith Gowda et al 28 The NF stream across a bent surface with exponential heating was studied by Punith Gowda et al 29 Dey et al 30 investigated the numerical calculation of heat transport in the stream of dusty fluid across a permeable elastic curved surface Naveen Kumar et al 31 deliberated the Stefan blowing impact on the convection flow of NF across a curved surface.…”
Section: Introductionmentioning
confidence: 99%